Solutions of Integral Nonclassical Ordinary Differential Equations Via Contractor Maps - Bishop, S. A.; Eke, K. S.; Akewe, H.; Okeke, G. (Communications in Mathematics and Applications, 2018)
Existence of a unique and bounded stochastic solution of integral nonclassical ordinary differential equation is studied using the method of integral contractor operators.